Development of a Collaborative Scheduling System of Offshore Platform Project Based on Multiagent Technology. (4th November 2014) - Li, Jinghua; Li, Lingyao; Yang, Boxin; Zhou, Qinghua
Abstract : Aimed at enhancing the effectiveness and efficiency for offshore platform project scheduling, a multiagent collaborative scheduling model based on the analysis of distributed offshore platform project scheduling was proposed. The functional definitions and internal structure of agents in the proposed system were analyzed. Moreover, in order to explore the cooperative way of agents, communication mechanism was presented and a negotiation model was elaborated. Then, system architecture and hardware architecture were constructed to lay a foundation to develop the collaborative scheduling system. Finally, an intelligent algorithm based on Bayesian method was designed to verify the negotiation model and a prototype system was developed to test the feasibility and rationality.